Host-country headquarters and an MNE's subsequent within-country diversifications - Ma, Xufei; Delios, Andrew (Journal of International Business Studies, 2010)
We propose that the establishment of a host-country headquarters (HCHQ) in a large emerging market can be viewed as part of a multinational enterprise's (MNE) political strategy to facilitate its within-country diversifications by reducing institutional intervention of the host government. Using a sample of MNEs in China in the period 1979–2005, we find that MNEs with an HCHQ had a greater number of subsequent diversifications in China, as compared with those MNEs without an HCHQ. This effect was more prominent when the diversifications were in domains with a higher level of institutional intervention.